Analysis of Ardeidae Bird Feedin The Coastal Ecosysrtem of Johan Pahlawan Sub-District West Aceh Regency - Farza Safirda; Abdullah Abdullah; Muhibbuddin Muhibbuddin; Ismul Huda; Devi Syafrianti (Universitas Syiah Kuala, 2020)
Study aims to determined know type Ardeidae bird feed in coastal ecosystem area of Johan Pahlawan District, West Aceh Regency. Research on Analysis of Ardeidae Bird Feedin The Coastal Ecosysrtem of Johan Pahlawan Sub-District West Aceh Regency carried out from July 2020. The method used is roaming method of diversity of bird feed species was observed and cleavage was carried out in the bird's stomach in the Coastal Coastal Ecosystem in Johan Pahlawan District, West Aceh Regency. The data obtained were analyzed descriptively. The results obtained 5 species, namely Ardea cinerea, Ardeola speciosa, Egretta alba, Egretta garzetta and Bubulcus ibis with the type of feed in the form of animals that are on the forest floor such as small fish, grasshoppers, crabs, frogs or frogs, small insects that live in water, flies and other types of invertebrates and vertebrates.